THE ROLE OF DA'WAH IN OVERCOMING SOCIAL PROBLEMS: PERAN DAKWAH DALAM MENGATASI MASALAH SOSIAL - Madeni; Agus, Agusman (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
This paper aims to describe the role of da'wah in overcoming social problems as well as provide a better understanding of the importance of da'wah in that context. The method used in this writing is literature analysis, with reference to sources of religious texts, academic studies, and related research. The result of this writing is a deeper understanding of the role of da'wah in dealing with social problems, such as poverty, violence, social injustice, and global injustice. Through da'wah, Muslims can provide education, empowerment, and assistance to those who are marginalized, promote peace, tolerance, justice, and take part in efforts to build a better world. The impact of this paper is to provide new insights to readers about the importance of da'wah in dealing with social problems. It can also inspire Muslims and society in general to get involved in efforts to address social problems in their neighborhoods. In addition, this paper can be a reference for researchers, academics, and da'wah practitioners in developing more effective strategies in dealing with social problems.